Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Explore thousands of questions and answers from a knowledgeable community of experts on our user-friendly platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To simplify the expression [tex]\(\sqrt{252 x^8 y^{19}}\)[/tex], follow these steps:
1. Break down the expression under the square root:
[tex]\[ \sqrt{252 x^8 y^{19}} \][/tex]
2. Factorize the constant and the variables separately inside the square root:
- For the constant [tex]\(252\)[/tex]:
[tex]\[ 252 = 2^2 \times 3^2 \times 7 \][/tex]
So,
[tex]\[ \sqrt{252} = \sqrt{2^2 \times 3^2 \times 7} = \sqrt{(2 \times 3)^2 \times 7} = \sqrt{36 \times 7} = 6\sqrt{7} \][/tex]
- For the variable [tex]\(x^8\)[/tex]:
[tex]\[ \sqrt{x^8} = x^{8/2} = x^4 \][/tex]
- For the variable [tex]\(y^{19}\)[/tex]:
[tex]\[ y^{19} = y^{18} \cdot y = (y^9)^2 \cdot y \][/tex]
Which means,
[tex]\[ \sqrt{y^{19}} = \sqrt{(y^9)^2 \cdot y} = y^9 \sqrt{y} \][/tex]
3. Combine these simplified parts together:
- The constant part [tex]\(6\sqrt{7}\)[/tex]
- The simplified variable [tex]\(x^4\)[/tex]
- The simplified variable [tex]\(y^9\sqrt{y}\)[/tex]
Therefore, the overall simplified expression is:
[tex]\[ 6 \sqrt{7} \cdot x^4 \cdot y^9 \cdot \sqrt{y} \][/tex]
4. Combine the results into a single expression:
[tex]\[ \boxed{6 \sqrt{7} x^4 y^9 \sqrt{y}} \][/tex]
1. Break down the expression under the square root:
[tex]\[ \sqrt{252 x^8 y^{19}} \][/tex]
2. Factorize the constant and the variables separately inside the square root:
- For the constant [tex]\(252\)[/tex]:
[tex]\[ 252 = 2^2 \times 3^2 \times 7 \][/tex]
So,
[tex]\[ \sqrt{252} = \sqrt{2^2 \times 3^2 \times 7} = \sqrt{(2 \times 3)^2 \times 7} = \sqrt{36 \times 7} = 6\sqrt{7} \][/tex]
- For the variable [tex]\(x^8\)[/tex]:
[tex]\[ \sqrt{x^8} = x^{8/2} = x^4 \][/tex]
- For the variable [tex]\(y^{19}\)[/tex]:
[tex]\[ y^{19} = y^{18} \cdot y = (y^9)^2 \cdot y \][/tex]
Which means,
[tex]\[ \sqrt{y^{19}} = \sqrt{(y^9)^2 \cdot y} = y^9 \sqrt{y} \][/tex]
3. Combine these simplified parts together:
- The constant part [tex]\(6\sqrt{7}\)[/tex]
- The simplified variable [tex]\(x^4\)[/tex]
- The simplified variable [tex]\(y^9\sqrt{y}\)[/tex]
Therefore, the overall simplified expression is:
[tex]\[ 6 \sqrt{7} \cdot x^4 \cdot y^9 \cdot \sqrt{y} \][/tex]
4. Combine the results into a single expression:
[tex]\[ \boxed{6 \sqrt{7} x^4 y^9 \sqrt{y}} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.